Assessment and Translation of the Antibody-in-Lymphocyte Supernatant (ALS) Assay to Improve the Diagnosis of Enteric Fever in Two Controlled Human Infection Models and an Endemic Area of Nepal - Darton, Thomas C.; Jones, Claire; Dongol, Sabina; Voysey, Merryn; Blohmke, Christoph J.; Shrestha, Rajendra; Karkey, Abhilasha; Shakya, Mila; Arjyal, Amit; Waddington, Claire S.; Gibani, Malick; Carter, Michael J.; et al. (Frontiers in Microbiology, 2017)
New diagnostic tests for enteric fever are urgently needed to assist with timely antimicrobial treatment of patients and to measure the efficacy of prevention measures such as vaccination. In a novel translational approach, here we use two recently developed controlled human infection models (CHIM) of enteric fever to evaluate an antibody-in-lymphocyte supernatant (ALS) assay, which can detect recent IgA antibody production by circulating B cells in ex vivo mononuclear cell culture. We calculated the discriminative ability of the ALS assay to distinguish diagnosed cases in the two CHIM studies in Oxford, prior to evaluating blood culture-confirmed diagnoses of patients presenting with fever to hospital in an endemic areas of Kathmandu, Nepal. Antibody responses to membrane preparations and lipopolysaccharide provided good sensitivity (>90%) for diagnosing systemic infection after oral challenge with Salmonella Typhi or S. Paratyphi A. Assay specificity was moderate (~60%) due to imperfect sensitivity of blood culture as the reference standard and likely unrecognized subclinical infection. These findings were augmented through the translation of the assay into the endemic setting in Nepal. Anti-MP IgA responses again exhibited good sensitivity (86%) but poor specificity (51%) for detecting blood culture-confirmed enteric fever cases (ROC AUC 0.79, 95%CI 0.70–0.88). Patients with anti-MP IgA ALS titers in the upper quartile exhibited a clinical syndrome synonymous with enteric fever. While better reference standards are need to assess enteric fever diagnostics, routine use of this ALS assay could be used to rule out infection and has the potential to double the laboratory detection rate of enteric fever in this setting over blood culture alone.